Detection of a novel killer-cell immunoglobulin-like receptor allele - KIR3DL1*0150207 - in Asian individuals - Wang, L; Yan, H; Dong, T; Rowland-Jones, S; Yindom, L (Blackwell Publishing Ltd, 2014)
KIR3DL1*0150207 differs from KIR3DL1*0150201 at five nucleotide positions in introns 2, 3, 4 and 5, respectively. © 2014 John Wiley and Sons A/S. Published by John Wiley and Sons Ltd.